Effect of Erwinia amylovora infection on peroxidase enzyme activity in resistant apple cultivars - Kása, K.; Hevesi, M.; G. Tóth, M.; Stefanovits-Bányai, É. (International Journal of Horticultural Science, 2004)
Two apple cultivars that display enhanced resistance to fire blight (causal agent: Erwinia amylovora) were selected. The aim of the present study was to characterize the peroxidase (POD) enzyme activity of `Szemes alma' (a historical cultivar) and MR-03, (a Hungarian multiresistant hybrid of 'Prima') and compare them to susceptible 'Jonathan M 40' and resistant 'Remo' controls. Peroxides enzyme activity during E. amylovora infections was investigated in artificially infected apple shoots. Increases in enzyme activities were observed in a `Jonathan M40' and in 'Remo', MR-03, `Szemes alma' cultivars. There was a consistent relationship between total enzyme activity and fire blight disease severity. High activity of the peroxidase was positively correlated with the degree of resistance to fire blight. A general hypothesis that POD activity is related to fire blight susceptibility/resistance is supported by our results.